Answer:
6xy²+7-x²y²-5x²y+3x²y²=6x²+7+2x²y²-5x²y
<h3>
Answer: 2x^2 + 6x - 4</h3>
=================================
Work Shown:
f(x) - g(x) = [ f(x) ] - [ g(x) ]
f(x) - g(x) = ( 3x^2+x-3) - ( x^2-5x+1 )
f(x) - g(x) = 3x^2+x-3 - x^2+5x-1
f(x) - g(x) = (3x^2-x^2) + (x+5x) + (-3-1)
f(x) - g(x) = 2x^2 + 6x - 4
Answer:
20? i dont know hopefully im right
Step-by-step explanation:
You plug in 1,2,3 and so on in the X and you graph , i think
Answer:
A.
Step-by-step explanation:
The first number is 2, so 2 must be plotted on the X radius (because it goes by X first). B plots X on the Y axis so therefore, by process of elimination, A is the answer.